Exploring the Effect of Polypyridyl Ligands on the Anticancer Activity of Phosphorescent Iridium(III) Complexes: From Proteosynthesis Inhibitors to Photodynamic Therapy Agents - Pracharova, Jitka; Vigueras, Gloria; Novohradsky, Vojtech; Cutillas, Natalia; Janiak, Christoph; Kostrhunova, Hana; Kasparkova, Jana; Ruiz, José; Brabec, Viktor (Chemistry (Weinheim an der Bergstrasse, Germany), 2018)
A series of five kinetically inert bis-cyclometalated IrIII complexes of general formula [Ir(C^N)2 (N^N)][PF6 ] [C^N=2-phenyl-1-[4-(trifluoromethyl)benzyl]-1H-benzo[d]imidazol-κN,C; N^N=1,10-phenanthroline (phen, 1), dipyrido[3,2-d:2',3'-f]quinoxaline (dpq, 2), dipyrido[3,2-a:2',3'-c]phenazine (dppz, 3), benzo[i]dipyrido[3,2-a:2',3'-c]phenazine (dppn, 4), and dipyrido[3,2-a:2',3'-c]phenazine-10,11-imidazolone (dppz-izdo, 5)] were designed and synthesized to explore the effect of the degree of π conjugation of the polypyridyl ligand on their toxicity in cancer cells. We show that less-lipophilic complexes 1 and 2 exhibit the highest toxicity [sub-micromolar inhibitory concentration (IC50 ) values] in A2780, HeLa, and MCF-7 cancer cells, and they are markedly more efficient than clinically used platinum drugs. It is noteworthy that the investigated Ir agents display the capability to overcome acquired and inherent resistance to conventional cisplatin (in A2780cisR and MCF-7 cells, respectively). We demonstrate that the Ir complexes, unlike clinically used platinum antitumor drugs, do not kill cells through DNA-damage response. Rather, they kill cells by inhibiting protein translation by targeting preferentially the endoplasmic reticulum. Our findings also reveal that the toxic effect of the Ir complexes can be significantly potentiated by irradiation with visible light (by more than two orders of magnitude). The photopotentiation of the investigated Ir complexes can be attributed to a marked increase (≈10-30-fold) in intracellular reactive oxygen species. Collectively, these data highlight the functional diversity of antitumor metal-based drugs and the usefulness of a mechanism-based rationale for selecting candidate agents that are effective against chemoresistant tumors for further preclinical testing.
Keywords: polymery; Animals; Ligands; pyridiny; Polymers; zvířata; anticancer agents; Antineoplastic Agents; conjugation; protinádorové látky; iridium; protein design; Pyridines; cell growth; ligandy